2004
DOI: 10.1074/jbc.m311912200
|View full text |Cite
|
Sign up to set email alerts
|

p53-regulated Transcriptional Program Associated with Genotoxic Stress-induced Apoptosis

Abstract: By using a genome-wide approach, we sought the identification of p53-regulated genes involved in cellular apoptosis. To this end, we assessed the transcriptional response of HCT116 colorectal cancer cells during apoptosis induced by the anticancer drug 5-fluorouracil as the function of p53 status, and we identified 230 potential targets that are regulated by p53. Previously identified p53 targets known to be involved in growth arrest and apoptosis were observed to be induced, thus validating the approach. Stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
137
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(148 citation statements)
references
References 53 publications
10
137
1
Order By: Relevance
“…4). Many genes are known to be regulated in a cell-specific and insult-specific manner [14,15], however the data here suggests that FLJ11259 is regulated in a p53-dependent manner in a variety of cell types and by at least two distinct DNA damaging agents, cisplatin and as previously shown, etoposide [6]. This supports a potential role for FLJ11259 in the biological response of tumors to chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 33%
“…4). Many genes are known to be regulated in a cell-specific and insult-specific manner [14,15], however the data here suggests that FLJ11259 is regulated in a p53-dependent manner in a variety of cell types and by at least two distinct DNA damaging agents, cisplatin and as previously shown, etoposide [6]. This supports a potential role for FLJ11259 in the biological response of tumors to chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 33%
“…These results are consistent with those from previously published microarray studies. 11,24,25 Saller et al first identified CYFIP2 (also known as PIR121) as a candidate p53 target gene whose mRNA was up regulated 5.3X by wild-type p53, 15.3X by a pro-apoptotic p53-121F mutant, and not induced in response to an anti-apoptotic p53-277R mutant, respectively, when stably expressed under TET control in H1299 cells or adenovirally expressed in Saos-2 (null for p53) or U2OS (expressing WT p53) cells. Using the nucleotide analog 5-fluorouracil, a DNA damage inducing chemotherapeutic drug, Kho et al detected a 2X increase in CYFIP2 mRNA by microarray in HCT116 cells in a p53-dependent manner, suggesting that CYFIP2 can be induced by endogenous p53.…”
Section: Discussionmentioning
confidence: 99%
“…The identity and associated function of each gene is provided in Table 1. Notably, 25 of the 46 induced genes have previously been identified as p53 target genes (Kannan et al, 2001;Sax and El-Deiry, 2003;Kho et al, 2004) (bold in Table 1), including nine of the top 10 genes ranked according to fold-change. The exception is the hypothetical protein FLJ11259, which is a potential novel p53 target.…”
Section: Microarray Analysis Uncovers Prominent P53 Target Gene Inducmentioning
confidence: 99%
“…(2) Indicates evidence for p53 target gene based on previous p53-specific microarray (Kannan et al, 2001;Sax and El-Diery, 2003;Kho et al, 2004). (NA) Indicates the information concerning a p53 target is not available.…”
Section: Microarray Analysis Uncovers Prominent P53 Target Gene Inducmentioning
confidence: 99%